Studi Pemanfaatan Formulasi Daun Sirsak, Benalu Ketapang, Rumput Teki, Dan Kunyit Putih Pada Minuman Fungsional Dengan Fermentasi Bakteri Lokal - Lorenta Indrianto; Sukardi; Istifar Yogi Prayogi (Food Technology and Halal Science Journal, 2026)
Abstract. Herbal drinks are drinks rich in bioactive ingredients such as antioxidants, flavonoids, and phenols that are beneficial for health such as having anticancer, anti-inflammatory, and antimicrobial potential. This study aims to provide the effect of the combination formulation of soursop leaves, mistletoe ketapang, nutsedge, and white turmeric on the chemical and sensory characteristics of functional drinks fermented using local bacteria. The research design used was a 1-factor Randomized Block Design (RBD) with 3 formulations (formulation 1, formulation 2, and formulation 3). The data obtained were analyzed using analysis of variance (ANOVA) at a significance level of 5%. If there is a significant difference, then it is continued with the Tukey test. The results showed that the results of antioxidants, total phenols, and flavonoids had a significant effect. The formulation with the highest proportion of white turmeric (160 g) produced the highest antioxidant activity (74.74%), total phenol content (5.29 mg GAE/ml), and flavonoids (0.080 mg QE/ml). The pH value decreased significantly from 4.04 to 3.41, indicating successful fermentation. Organoleptic tests showed that all formulations were accepted by panelists on a neutral to slightly favorable scale. The conclusion of this study is that the formulation with the highest white turmeric content significantly contributed to the increase in bioactive compounds and has the potential to be developed as a functional beverage based on natural fermentation Abstract. Herbal drinks are drinks rich in bioactive ingredients such as antioxidants, flavonoids, and phenols that are beneficial for health such as having anticancer, anti-inflammatory, and antimicrobial potential. This study aims to provide the effect of the combination formulation of soursop leaves, mistletoe ketapang, nutsedge, and white turmeric on the chemical and sensory characteristics of functional drinks fermented using local bacteria. The research design used was a 1-factor Randomized Block Design (RBD) with 3 formulations (formulation 1, formulation 2, and formulation 3). The data obtained were analyzed using analysis of variance (ANOVA) at a significance level of 5%. If there is a significant difference, then it is continued with the Tukey test. The results showed that the results of antioxidants, total phenols, and flavonoids had a significant effect. The formulation with the highest proportion of white turmeric (160 g) produced the highest antioxidant activity (74.74%), total phenol content (5.29 mg GAE/ml), and flavonoids (0.080 mg QE/ml). The pH value decreased significantly from 4.04 to 3.41, indicating successful fermentation. Organoleptic tests showed that all formulations were accepted by panelists on a neutral to slightly favorable scale. The conclusion of this study is that the formulation with the highest white turmeric content significantly contributed to the increase in bioactive compounds and has the potential to be developed as a functional beverage based on natural fermentation